APLIKASI MOBILE PENJUALAN PRODUK PADA HANAKA CONCEPT STORE DENGAN FITUR GAMIFICATION - Putu Agus Indra Purnama; Duman Care Khrisne; I Gusti Komang Diafari Djuni (Program Studi Teknik Elektro UNUD, 2017)
Hanaka concept store is a company engaged in the field of fashion in Bali, which was established since March 19, 2013 which is located at Jalan Tukad Pakerisan No. 54 Denpasar, Bali. Competition in the world of fashion makes Hanaka concept store is required to be different in terms of fashion and product marketing. This study aims to build mobile product-based product sales system at Hanaka Concept Store. The system is built using the method of gamification in order to make the product marketing process becomes more attractive to the customer. Gamification methods contained in this application in the form of providing point to the activities undertaken by the customer either the transaction product order or quest-quest. From the results of system implementation and charging questionnaires to customers, get a score of 4.41 which in this case strongly agree with the existence of mobile applications that feature gamification.